Review of the Adequacy of the Fund's Precautionary Balances. (Policy Papers; Policy Paper, 2016)
This paper reviews the adequacy of the Fund's precautionary balances, using the framework approved by the Board in 2010. The review takes place on the standard two-year cycle. The paper discusses developments since the last review in 2014 and revisits several issues discussed at that time. The framework provides an indicative range for the target for precautionary balances linked to credit outstanding, and allows for judgment in setting this target. A reserve coverage ratio of 20-30 percent draws on approaches in other IFIs, adapted to the circumstances of the Fund, and is a guide for determining the target. At the same time, Directors have emphasized the continued importance of judgment and Board discretion in light of a broad assessment of financial risks facing the Fund.